2015
DOI: 10.5935/1676-2444.20150003
|View full text |Cite
|
Sign up to set email alerts
|

Level of reactivity of IgM anticardiolipin antibodies in preeclampsia: a likely early serologic marker

Abstract: The purpose of this study was to measure the level of anticardiolipin antibodies in preeclamptic pregnant women to verify a possible association between the presence of these antibodies and the development of the syndrome. A total of 36 pregnant women with preeclampsia and 19 women with normal pregnancy were evaluated. Anticardiolipin antibodies were determined by enzyme immunoassay. The reactivity level of anticardiolipin antibodies was significantly higher in the preeclamptic group, with a significance level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…The mean Although there are not much previous evidences that suggested a positive relation of anti-cardiolipin antibody with preeclampsia, some earlier studies showed the similar relation which is consistent with these findings. 18-20 Pereira et al (2015) showed that anticardiolipin IgM antibody was detected in 13.9% women with preeclampsia and the level was significantly higher in preeclampsia group compared to control. 19 Ferrer-Oliveras et al (2012) showed similar findings.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The mean Although there are not much previous evidences that suggested a positive relation of anti-cardiolipin antibody with preeclampsia, some earlier studies showed the similar relation which is consistent with these findings. 18-20 Pereira et al (2015) showed that anticardiolipin IgM antibody was detected in 13.9% women with preeclampsia and the level was significantly higher in preeclampsia group compared to control. 19 Ferrer-Oliveras et al (2012) showed similar findings.…”
Section: Discussionmentioning
confidence: 97%
“…18-20 Pereira et al (2015) showed that anticardiolipin IgM antibody was detected in 13.9% women with preeclampsia and the level was significantly higher in preeclampsia group compared to control. 19 Ferrer-Oliveras et al (2012) showed similar findings. There was significant differences of anticardiolipin IgM antibody between the preeclampsia group and the controls (8.1 vs 1.2%, p=0.041).…”
Section: Discussionmentioning
confidence: 97%